Biological Activities of Wild Asparagus (Asparagus acutifolius L.) - Arzu Kaska; Nahide Deniz; Ramazan Mammadov (International Journal of Secondary Metabolite)
Asparagus acutifolius L. (wild asparagus) is an edible plant species that is widely distributed throughout the Mediterranean. This study was designed to investigate the phenolic compounds, antioxidant, and cytotoxic activities of ethanol and water extracts of different parts (fruits and leaves) of A. acutifolius. The antioxidant activities of these extracts were analyzed using scavenging methods (DPPH and ABTS scavenging activity), the β-carotene/linoleic acid test system and the phosphomolybdenum method. Among the evaluations of the ethanol and water extracts of the different parts of A. acutifolius, the ethanol extract of the leaves was shown to have the highest amount of radical scavenging activities (DPPH, 0.383 mg/mL and ABTS, 0.145 mg/mL). Each extract of A. acutifolius exhibited strong antioxidant capacities with the β-carotene/Linoleic acid test system. For the phosphomolybdenum method, the antioxidant capacity of the extracts was in the range of 8.89-45.29 µg/mg and each extract exhibited high cytotoxic activities. The results will provide additional information for future studies on the biological activities of A. acutifolius, while also helping us to understand the importance of this species.